Temporal changes in the transcriptome profile of Macrobrachium rosenbergii in response to decapod iridescent virus 1 infection - Hao, Jingwen; Jie, Yukun; Lu, Zhibin; Ye, Tiantian; Meng, Jilun; Liu, Cui; Yan, Junjun; Zheng, Yutong; Dong, Zaijie; Gu, Zhimin (Frontiers in Immunology, 2025)
The farming of Macrobrachium rosenbergii faces significant challenges due to infections caused by Decapod iridovirus 1 (DIV1). To gain deeper insights into the dynamic immune regulatory processes of M. rosenbergii in response to DIV1 infection, RNA sequencing (RNA-seq) was employed to profile the transcriptome in the hepatopancreas at 24, 48, 72, and 96 hours post-infection (hpi). Time-course analysis revealed 3,339 differentially expressed genes (DEGs), which exhibited distinct expression patterns across various stages of infection. At 24 hpi and 48 hpi, the top 20 enriched pathways included 3 immunity-related pathways (Lysosome, Phagosome, C-type lectin receptor signaling) and 7 metabolism-related pathways at 24 hpi, and 5 metabolism-related pathways at 48 hpi. In contrast, in the later stages of infection (72 hpi), 13 of the top 17 enriched pathways associated with DEGs were metabolism-related, including those involved in antioxidant defense, such as the Peroxisome, Cysteine and methionine metabolism, and Glutathione metabolism. At 96 hpi, pathways related to ECM-receptor interaction, Purine metabolism, and Lysosome were significantly enriched. Among the DEGs, a total of 16 genes were consistently identified across all time points, with 14 of these genes, including alpha-2-macroglobulin-like, alpha-amylase 1-like, putative aldolase class 2 protein PA3430, platelet-derived growth factor subunit B-like, serum amyloid A-5 protein-like, phenoloxidase-activating enzyme-like, pantetheinase-like, and perlucin-like protein, demonstrating sustained upregulation at all time points. In contrast, the gene encoding rhodanese domain-containing protein CG4456-like was consistantly downregulated. Additionally, weighted gene co-expression network analysis (WGCNA) indicated several hub genes that were tightly connected to intercellular communication, such as innexin shaking-B-like and innexin inx3-like, and endochitinase A1-like. The gene expression changes varied over time, exhibiting a dynamic, time-dependent pattern that underscores the complexity of host-pathogen interactions. These results provide new insights into the cellular mechanisms influenced by DIV1 throughout the infection process, offering valuable knowledge for developing virus control strategies in shrimp aquaculture.